2016
DOI: 10.1089/neu.2015.4237
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Phosphorylated Neurofilament Heavy Subunit as a Predictive Marker for Outcome in Adult Patients after Traumatic Brain Injury

Abstract: The serum phosphorylated neurofilament heavy subunit (pNF-H) is a nervous system-specific protein that is released from damaged neural tissue after traumatic brain injury (TBI). The aim of this study was to elucidate the usefulness of serum pNF-H as a predictive marker for the outcome of patients after TBI. Patients with TBI (Glasgow Coma Scale score of 13 or less on admission) were included. Patients who were younger than age 18, dependent on others for daily activities before injury, pregnant, or who were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Although there is an increasing evidence that NfH could predict severity and evolution in the pathology associated with neuroaxonal damage, there is still not sufficient data that this marker could be used in current practice for evaluation of patients with cerebral ischemia. Besides traumatic brain injury (8,9) and acute intracerebral hemorrhage (10), in the literature there are only a few studies regarding peripheral NfH in ischemic stroke. Traenka et al found that plasma NfL (light chains) concentration correlates with stroke severity mirrored by NIHSS in stroke occurred after cervical artery dissection, and NfL levels significantly associated with poor outcome evaluated after 3 months, but in this study the median time for serum sampling was 6 days, (IQR 3-9.5 days) (11).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an increasing evidence that NfH could predict severity and evolution in the pathology associated with neuroaxonal damage, there is still not sufficient data that this marker could be used in current practice for evaluation of patients with cerebral ischemia. Besides traumatic brain injury (8,9) and acute intracerebral hemorrhage (10), in the literature there are only a few studies regarding peripheral NfH in ischemic stroke. Traenka et al found that plasma NfL (light chains) concentration correlates with stroke severity mirrored by NIHSS in stroke occurred after cervical artery dissection, and NfL levels significantly associated with poor outcome evaluated after 3 months, but in this study the median time for serum sampling was 6 days, (IQR 3-9.5 days) (11).…”
Section: Discussionmentioning
confidence: 99%
“…In TBI, serum-pNFH levels at 72h after hospital arrival were significantly higher than at 24h after arrival. Serum-pNFH at 24 hours after injury was shown to be a good predictor of fatal outcome in patients with TBI [148].…”
Section: Neurofilaments In Acute Brain Injuriesmentioning
confidence: 95%
“…NF subunits have been found in the corpus callosum of TBI patients [ 96 ]. A recent study by Shibahashi et al [ 99 ] investigated the usefulness of serum phosphorylated neurofilament heavy subunit (pNF-H) at 24 and 72 h after TBI, as a predictive marker for the outcome (vegetative state or death) of patients at 6 months. Conversely, Neurofilament Light chain (NF-L) protein serum level has been recently advocated as a potentially promising predictor of the 12 months neurological outcome of patients with an MRI demonstrated DAI [ 100 ].…”
Section: Pathological Anatomy and Morphologic Findingsmentioning
confidence: 99%